Biomass yield and nutritional quality of three forages harvested at two cutting height - Elizondo Salazar, Jorge Alberto (2017)
The objective of this experiment was to determine the effect of cutting height on yield and nutritional quality of three forage species used for feeding dairy cattle. The study was carried out at the “Alfredo Volio Mata” Experiment Station of the University of Costa Rica. The evaluated species were: native corn (Zea mays), black sorghum (Sorghum almum) and king grass cultivar Taiwan (Pennisetum purpureum); these three species were harvested at two different cutting heights (15 and 45 cm above ground). Green forage yield was significantly different (P<0.05) within each of the species and dry matter (DM) yield was reduced between 17 to 42% when cutting height was increased. When cutting height was done at 15 cm above ground, corn, black sorghum and Taiwan yielded 51.3, 31.4 and 70.9 t/ha/ cycle, respectively. With regard to DM, the forage species that yielded the most when harvested at 15 cm above ground was Taiwan grass, with 11.6 t/ha/cycle, while the forage species that yielded the least when harvested at 45 cm was corn with only 5.4 t/ha. Black sorghum signi cantly (P<0.05) improved its nutritive value when cutting height was increased. DM concentration increased from 22.79 to 25.53%, crude protein also increased from 8.24 to 12.90%, meanwhile neutral detergent fiber decreased from 63.69 to 59.47% and acid detergent fiber also decreased from 43.15 to 37.30%.